Effects of Diet Containing MOL-Fermented Oil Palm Fronds and Amino Acid Supplementation on the Performance and Digestibility of Local Crossbred Bulls - Musa Seno Ibrahim; Nevy Diana Hanafi; Ma’ruf Tafsin; Desti Prestasi Zendrato (Animal Husbandry Department, The Faculty of Agriculture, Universitas Syiah Kuala, 2026)
The use of oil palm fronds (OPF) in cattle diets is limited by their high fiber content and low digestibility. This study evaluated the effects of MOL-fermented OPF supplemented with DL-methionine and L-lysine HCl on the performance, digestibility, and economic efficiency of local crossbred bulls. The study was conducted from March to May 2019 at the Marihat Perkasa Cattle Farm in the Simalungun Regency of North Sumatra, Indonesia. A total of 12 local crossbred bulls aged 12–18 months with an average initial body weight of 211.17 ± 39.04 kg were arranged in a randomized block design with four dietary treatments and three body weight blocks. The rations were formulated as complete feeds containing 45% roughage and 55% concentrate feed. Treatments were as follows: T0 = concentrate + field grass, T1 = concentrate + unfermented OPF, T2 = concentrate + MOL-fermented OPF, and T3 = concentrate + MOL-fermented OPF supplemented with 0.25% DL-methionine and 0.25% L-lysine HCl based on the total ration as-formulated basis. For T2 and T3, OPF was anaerobically fermented for seven days using 300 mL MOL inoculum per 50 kg fresh OPF, with 1% urea and 4% molasses. The cattle were adapted to the diets for two weeks before data collection, followed by a 60-day feeding trial. Dietary treatment significantly affected all variables (P<0.05). T3 produced the highest feed intake (7.48 ± 0.316 kg/head/day), average daily gain (1.27 ± 0.205 kg/head/day), dry matter digestibility (72.23 ± 6.58%), organic matter digestibility (73.65 ± 6.26%), and income over feed cost (1,438,012 IDR/head), as well as the lowest feed conversion ratio (8.61 ± 1.03). In conclusion, MOL-fermented OPF supplemented with 0.25% DL-methionine and 0.25% L-lysine HCl improved the performance, digestibility, and economic efficiency of local crossbred bulls.